COMPARISON OF hCG AND GnRH FOR SYNCHRONIZATION OF THE FOLLICULAR WAVE IN SAANEN GOATS DURING THE BREEDING SEASON: hCG and GnRH for synchronization of the follicular wave in goats - Dogan, Ibrahim; Toker, Mehmed Berk; Aktar, Ahmet; Yilmaz, Mehmet Melih; Huraydin, Oguzhan; Udum, Duygu (Slovenian Veterinary Research, 2024)
This study aimed to compare the effects of a single dose of GnRH or hCG administered at the beginning of the short-term oestrus synchronization protocol on ≥4 mm diameter follicles in Saanen goats during the breeding season. The goats es-trus cycles were synchronized with intravaginal sponges containing 60 mg of medroxy-progesterone acetate for five days. Additionally, 1 ml of physiological saline solution (control-group; n=30), 0.004 mg of buserelin acetate (GnRH-group; n=31) or 150 IU of hCG (hCG-group; n=31) were injected intramuscularly to the goats during the sponges insertion. Transrectal ultrasonographic examination was performed immediately be-fore and 24 h after intravaginal sponge application into all goats and follicles with a diameter of ≥4 mm in the ovaries were counted. Blood samples were collected on the same days to determine serum progesterone (P4) and estradiol (E2) concentrations. At the first ultrasonographic examination, the percentages of ≥4 mm diameter follicles were 56.66% (17/30), 54.83% (17/31) and 70.96% (22/31) in the control, GnRH and hCG groups, respectively. The percentage of goats with reduced follicle diameters 24 h later was 29.41% (5/17), 52.94 (9/17) and 59.09% (13/22) in the same groups, respectively. The mean regression rates of follicle diameters between days 0 and 1 in each group were significantly different (P<0.05). Serum E2 concentrations were significantly differ-ent (P<0.05) between days 0 and 1 in hCG group. There were no differences in serum E2, P4 concentrations and mean regression rates in follicle diameters between days 0 and 1 for all groups. As a result, a significant relationship between the administration of hCG or GnRH and the reduction of large follicle diameters could not be established. Primerjava hCG in GnRH za sinhronizacijo folikularnega vala pri kozah Saanen med sezono parjenja Izvleček: Namen te študije je bil primerjati učinke enkratnega odmerka GnRH ali hCG danega na začetku kratkotrajnega protokola za sinhronizacijo estrusa na folikle s premerom ≥ 4 mm pri kozah pasme Saanen med sezono parjenja. Cikle estrusa pri kozah smo pet dni sinhronizirali z intravaginalnimi gobicami z vsebnostjo 60 mg medroksi progesteron ace-tata. Poleg tega smo jim v času vstavljanja gobic intramuskularno aplicirali 1 ml fiziološke fiziološke raztopine (kontrolna skupina; n=30), 0,004 mg buserelin acetata (skupina GnRH; n=31) ali 150 IU hCG (hCG-skupina; n=31). Neposredno pred in 24 ur po intravaginalni uporabi gobice smo pri vseh kozah opravili transrektalni ultrazvočni pregled in prešteli jajčne fo-likle s premerom ≥ 4 mm. Ob istih dnevih smo odvzeli tudi vzorce krvi za določitev serumskih koncentracij progesterona (P4) in estradiola (E2). Ob prvem ultrazvočnem pregledu so bili odstotki foliklov s premerom ≥ 4 mm 56,66 % (17/30) v kontrolni, 54,83 % (17/31) v GnRH in 70,96 % (22/31) v hCG skupini. Odstotek koz z zmanjšanim premerom foliklov 24 ur pozneje je bil 29,41 % (5/17) v kontrolni, 52,94 % (9/17) v GnRH in 59,09 % (13/22) v hCG skupini. Povprečna stopnja regresije premerov foliklov med dnem 0 in 1 se je pomembno razlikovala (P<0,05) v vseh skupinah. Koncentracija E2 v serumu se je med dnem 0 in 1 pomembno razlikovala (P<0,05) v skupini hCG. V serumskih koncentracijah E2 in P4 ter povprečni stopnji regresije v premeru foliklov med dnevi 0 in 1 ni bilo razlik v nobeni skupini. Posledično ni bilo mogoče potrditi povezave med dajanjem hCG ali GnRH ter zmanjšanjem premera velikih foliklov. Ključne besede: sinhronizacija estrusa; folikel; hCG; GnRH; koza